2020
DOI: 10.1073/pnas.1920478117
|View full text |Cite
|
Sign up to set email alerts
|

Ventral prostate and mammary gland phenotype in mice with complete deletion of the ERβ gene

Abstract: Disagreements about the phenotype of estrogen receptor β (ERβ) knockout mouse, created by removing the DNA-binding domain of the ERβ gene or interruption of the gene with a neocassette (Oliver Smithies ERβ knockout mice [ERβOS−/−]), prompted us to create an ERβ knockout mouse by deleting the ERβ gene with the use of CRISPR/Cas9 technology. We confirmed that the ERβ gene was eliminated from the mouse genome and that no ERβ mRNA or protein was detectable in tissues of this mouse. Overall the phenotype of the ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Furthermore, in a very recent work, Warner et al have reevaluated the role of ERβ, using the CRISPR/Cas9 technology to create an ERβ KO mouse model in which the entire gene has been deleted. These authors observed the formation of in situ ductal cancer in the prostate and mammary gland in ERβ KO mice, and then confirming an oncosuppressive role of this receptor [20].…”
Section: Of 28mentioning
confidence: 69%
“…Furthermore, in a very recent work, Warner et al have reevaluated the role of ERβ, using the CRISPR/Cas9 technology to create an ERβ KO mouse model in which the entire gene has been deleted. These authors observed the formation of in situ ductal cancer in the prostate and mammary gland in ERβ KO mice, and then confirming an oncosuppressive role of this receptor [20].…”
Section: Of 28mentioning
confidence: 69%
“…E2 is highly lipophilic and can easily pass from the periphery to the brain. In female mice older than 13 months, the reduction of oocyte follicles and the consequent decrease in blood E2 levels 46 could affect brain E2 status, that would depend mainly on brain local production, compromising E2-dependent neuroprotective mechanism 47 . The concept of an enhanced E2 signaling in the brain of Cyp46Tg females is also supported by the fact that Ers2 and Apod, an ERβ-specific target gene 48 , are increased in the hippocampus of these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Materials. The details of a mouse line with a constitutive knockout of the ERβ gene using CRISPR-Cas9−mediated gene editing was previously reported by our group (13).…”
Section: Methodsmentioning
confidence: 97%
“…When ERβ is completely removed from the mouse genome (ERβ crispr−/− mice), there is epithelial hyperplasia, fibroplasia, and stromal overgrowth and intra ductal cancerlike lesions in the VP. These phenotypes are accompanied by an increase in P63 and Ki67, and loss of Purα and DACH1, two AR repressors (13). Thus, activating ERβ in the VP should be considered to be a target for the treatment of early-stage PCa to prevent cancer progression.…”
mentioning
confidence: 99%